Respons Pertumbuhan dan Produksi Tanaman Sorgum (Sorghum bicolor (L.) Moenchterhadap Pemberian Mulsa dan Berbagai Metode Olah Tanah - Khairunnisa Khairunnisa; Ratna Rosanty Lahay; T. Irmansyah. (Universitas Sumatera Utara, 2015)
The research was conducted on Pasar 3 Padang Bulan, Medan about 25 m above sea level fromMay to September 2014. The research uses Split Plot Design with two treatment factors with threereplications. Main plots were soil tillage with two treatments, no-tillage (P0); perfect tillage (P) andthe subplot was mulching with four treatments, without mulch (M0); rice straw mulch (M);Thitonia mulch (M2); Imperata cylindrica mulch (M). The results showed that tillage treatmentsaffected significantly stem diameter ages 8 and 9 weak after plant but not significant affected onother parameters. Mulching treatment not affected significantly on all parameters. The interactionbetween two treatments affected significantly on plant height, number of leaves, and stem diameter.Keywords: soil tillage, mulching, sorghum. 311